Korea : : Unrest - Great Britain Embassy (Japan); Great Britain Foreign Office; National Archives (Great Britain); Adam Matthew Digital (Adam Matthew Digital, 1934)
Foreign Office file containing correspondence and memoranda relating to political unrest in Korea under Japanese administration and the rise of Communist activism